Gender, Racial, and Health Insurance Differences in the Trend of Implantable Cardioverter‐Defibrillator (ICD) Utilization: A United States Experience Over the Last Decade. Issue 2 (22nd January 2016) - Patel, Nileshkumar J.; Edla, Sushruth; Deshmukh, Abhishek; Nalluri, Nikhil; Patel, Nilay; Agnihotri, Kanishk; Patel, Achint; Savani, Chirag; Patel, Nish; Bhimani, Ronak; Thakkar, Badal; Arora, Shilpkumar; et al.
ABSTRACT: Prior studies have highlighted disparities in cardiac lifesaving procedure utilization, particularly among women and in minorities. Although there has been a significant increase in implantable cardioverter‐defibrillator (ICD) insertion, socioeconomic disparities still exist in the trend of ICD utilization. With the use of the Nationwide Inpatient Sample from 2003 through 2011, we identified subjects with ICD insertion (procedure code 37.94) and cardiac resynchronization defibrillator (procedure code 00.50, 00.51) as codified by the International Classification of Diseases, Ninth Revision, Clinical Modification . Overall, 1 020 076 ICDs were implanted in the United States from 2003 to 2011. We observed an initial increase in ICD utilization by 51%, from 95 062 in 2003 to 143 262 in 2006, followed by a more recent decline. The majority of ICDs were implanted in men age ≥65 years. Implantation of ICDs was 2.5× more common in men than in women (402 per million vs 163 per million). Approximately 95% of the ICDs were implanted in insured patients, and 5% were used in the uninsured population. There has been a significant increase in ICD implantation in blacks, from 162 per million in 2003 to 291 per million in 2011. We found a significant difference in the volume of ICD implants between the insured and the uninsured patient populations. Racial disparities have narrowed significantly in comparison with those noted in earlier studies and are now more reflective of the population demographics at large. On the other hand, significant gender disparities continue to exist.